Pengaruh Pemahaman Perpajakan terhadap Niat Melakukan Kecurangan oleh Calon Wajib Pajak - Dewi Kusuma Wardani; Atika Lestari (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine the effect of understanding taxation on the intention to commit fraud by prospective taxpayers. This study uses a quantitative description method and primary data using a questionnaire. The number of samples in this study were 100 student respondents at the Universitas Sarjanawiyata Tamansiswa Yogyakarta. Sampling in this study using convenience sampling technique. This study provides results that understanding taxation has a positive effect on the intention to commit fraud by prospective taxpayers. The results of this study are expected to be useful and useful for students of the University of Sarjanawiyata Tamansiswa as prospective taxpayers in the future. This study found that the understanding of taxation has a positive effect on the intention to commit fraud by prospective taxpayers. So that the understanding of taxation obtained in college has not been able to increase student awareness not to commit fraud. Therefore, it is hoped that the teaching of taxation will be improved so that in the future it can be implied and it is necessary to consider the factor of understanding taxation when making tax payments so that it can pass tax-abiding prospective taxpayers. Keywords: understanding of taxation, intention to commit fraud by prospective taxpayers.